INTERESTING VIEWERS ANALYSIS ON ADVERTISING AT TELEVISION (Case Study of Cigarette Ads for Viewers in the Surabaya Area) - Warsono, Warsono (UNIPA PRESS, 2020)
The increasing number of advertisers ontelevision, advertising is measured objectively.However, there are still many advertisementsthat fail, because advertising agencies do notdesign advertisements in the form of news. Toplace an ad, the company hires the services ofan advertising agency to design and managethe placement of its advertisements. To restoreclient confidence, an advertising agency mustbe able to increase creativity and selladvertising effectiveness to clients. So, whatthey have to do is create a truly effectiveadvertisement in accordance with what theywant, which aims to improve the image, statusand power of the advertisement they havedesigned. This study uses a factor analysismethod, from 25 question variables reduced to17 question variables. There are 8 variablesthat are wasted or considered not important.The 17 variables are included in the newfactors that are formed, the number of newfactors is 6 factors, namely: advertisingcomponents, attractiveness of advertising,advertising goals, style in the implementationof advertising messages, the psychologicalimpact of advertising, and display advertising.The six factors consisting of 17 variables orcomponents of advertising. After calculatingusing the frequency analysis contained indescriptive statistics, it can be seen that the adcomponent or ad variable that is most indemand by TV viewers is the humorous adcomponent with a percentage value of 50.7%